KADAR PROTEIN, AKTIVITAS ANTIOKSIDAN DAN SIFAT SENSORIS BOLU KUKUS DENGAN PENAMBAHAN TEPUNG KECAMBAH KACANG MERAH - Emi Maghfiroh; Siti Aminah; Yunan Kholifatuddin Sya'di (Jurnal Pangan dan Gizi, 2025)
Steamed sponge is one type of food product that is in great demand by the public. Red bean sprouts provide the latest variation on steamed cakes, which can be used to increase the nutritional value of protein content and the antioxidant activity of steamed cakes. The purpose of this study was to determine the protein content, antioxidant activity and sensory properties of steamed sponge cake with the addition of red bean sprout flour. The design used was RAL 1 variation, namely red bean sprout flour with concentration levels (0, 5, 10 and 15%). The variables analyzed included protein levels (micro kjeldahl), antioxidant activity (DPPH), sensory (hedonic). The results of the analysis showed that the addition of red bean sprout flour had an effect on protein content, antioxidant activity, sensory (color, taste, texture and aroma). The addition of 15% red bean sprout flour was the best treatment with panelists' preferred sensory assessment, protein content of 7%, antioxidant activity of 24.16% RSA.